Late-onset glucocorticoid-responsive circulatory collapse in premature infants - Shigeo Iijima (Elsevier, 2019)
Late-onset glucocorticoid-responsive circulatory collapse (LGCC) in infants is characterized by sudden onset of hypotension and/or oliguria, which is resistant to volume expanders and inotropes but responds rapidly to intravenous glucocorticoids. LGCC occurs after the first week of life mainly in relatively stable very low birth weight (VLBW) infants. In Japan, the incidence of LGCC is reported to be 8%. Relative adrenal insufficiency (AI) is considered the most likely cause of LGCC, but its detailed pathophysiology remains unclear. Intrinsic and extrinsic factors may affect the pathophysiological mechanism. LGCC should be recognized as one of the high-risk complications in VLBW infants and managed promptly and properly, because if it is not, it may cause life-long neurological problems. To diagnose relative AI, an accurate evaluation of adrenal function is necessary; however, the interpretation of basal serum cortisol levels is difficult in preterm infants after 7 days of life. To recognize LGCC, it is recommended that blood pressure and urine volume be carefully monitored, even outside of the transitional period. If no underlying causes are documented or volume expansion and inotropic support fail, intravenous hydrocortisone should be initiated, and an additional dose of hydrocortisone is required when the response is inadequate. There are few reports to verify or characterize LGCC and this phenomenon has not been recognized worldwide to date. This review summarizes the current knowledge about LGCC in premature infants and evaluates the most significant new findings regarding its pathophysiology, treatment, and prognosis. Key Words: adrenal insufficiency, circulatory collapse, glucocorticoid, hypotension, neonate